2y-3x-1=0

Simple and best practice solution for 2y-3x-1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y-3x-1=0 equation:


Simplifying
2y + -3x + -1 = 0
Reorder the terms:
-1 + -3x + 2y = 0
Solving
-1 + -3x + 2y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + -3x + 1 + 2y = 0 + 1
Reorder the terms:
-1 + 1 + -3x + 2y = 0 + 1
Combine like terms: -1 + 1 = 0
0 + -3x + 2y = 0 + 1
-3x + 2y = 0 + 1
Combine like terms: 0 + 1 = 1
-3x + 2y = 1
Add '-2y' to each side of the equation.
-3x + 2y + -2y = 1 + -2y
Combine like terms: 2y + -2y = 0
-3x + 0 = 1 + -2y
-3x = 1 + -2y
Divide each side by '-3'.
x = -0.3333333333 + 0.6666666667y
Simplifying
x = -0.3333333333 + 0.6666666667y

You can always share this solution

See similar equations:

| 4xy+x^2-3xy^2-y=-5 | | 3.1x+5.4=24 | | (3+5i)=(3-5i) | | 1.1x+19.5=43.7 | | .5x-5=-4 | | 4x-13.1=78.9 | | 10.1x+3.6=124.8 | | 10=-13x+4x | | x^5+4x=0 | | 28-3z=-7x | | (-5+4i)=(3+i) | | -48x^2-40x+48=0 | | Y^1=3cosx^3 | | 3(x-12)=48 | | 4.5x-18=27 | | 16x-51=413 | | lg(x^2-2)=lg^1x | | 8n=20+2n+6 | | -3i=(7i-5) | | 4.6x-63.5=-22.1 | | 8n=20(2n)+6 | | 8n=20+6(n-2) | | 16x-19=29 | | 8n=20+6n | | 8i=(14-9i) | | 2/4+= | | 5+(x+-12)=18 | | 13=-13x+2x | | 6(x-1)=3(5y-2)findy | | 0.5t*(8-t)=0.5t*t | | 6(x-1)=3(5y-2) | | 6-(-5+4i)=(-13-i) | | 2z+5=15 | | 0.5t*t=0.5t*(8-t) | | 4x+2-3x=14-6x | | 5=4x+2-x | | 10(x+20)=70 | | 14x-7x^2=0 | | 15y-6x=0 | | (3+2i)=(5-7i) | | -12720+20=6000 | | 5-3a=-10 | | -12720+20=600 | | 2p+1.71+2.1=2.20 | | 4p-4=-2p+4 | | 7=-5+v | | 12=-7+d | | 4p-4=2p+4 | | 9p-11=-3+7 | | 30=6f | | 2|x-5|-3=15 | | 9p-11=-3p+7 | | 2w^2+11w+21=(w+7)2 | | 9p-11=-3 | | |3x-2|=24 | | -44=4k | | 9p-11=3p+7 | | 16n+21=12n-15 | | 5v^2+v-4=0 | | 4=-5+r | | (3x-1)*(2x+7)-(x+1)*(6x-5)=16 | | 11=9y-4y-4 | | 2p+3a=1.70 | | 6=-2+f | | 3b-4b=0 |


Related pages


whats a lcmprime factorization 98square root of 3249cos3x sin3xconvert percent to decimal calculatorwhat is twenty percent of fifty dollarsaplus cmcssadding fractions calculator with variablessolving quadratic equation calculatorroman numeral of 10000006x 3y 4f x tanx11.25 as a fractionlcm of 2 49x 2-4sin45 cos4536 prime factorization3000 rupees in dollarsbycxderivative of ln2x2cos2x-1 0what is prime factorization of 908y y8factor 3x 2 2x 5ln5 ln2factor x squared plus 4graph of 2x7-111gcf math calculatorwhat is the lcm of 9derivative of cos 3tsen 4xhow do you write 0.6 as a fraction1975 roman numeralsfactorise x squared xderivative of cos 5xcmcss aplussolve sinx sin2xwhat is 12.5 as a decimalhow do you write 0.75 as a fractioncosx secx cosxwrite the prime factorization of 24prime factorization of 25483-42x 3 y 3 3xy15 000 euros to dollarsderivative of 2 cosx2kxwhat is 3x squared74-253.75 as a fraction30 000 pounds in dollarsprime factorization for 46cot 2x2345678901differentiation of cos xlowest common denominator calculatorprime factors of 76what is the derivative of cos 2xlcm of 150what is the prime factorization of 344derivative ln x 3fraction calculator with solutionroman numerals 100-2008y8bxdxprime factorization of 164lcm generatorfind the prime factorization of 96sin 2x cos 2x 0i 3u equationderivative of lnxsimplify 8x 3 272x 5x 739.95 in dollars2sinxcosx 0gcf of 64 and 40prime factorization of 252gcf of 84